Chemical Analysis, Cytotoxicity and Antimicrobial Studies by Snapdragon: A Medicinal Plant - Riaz, Muhammad; Rasool, Nasir; Rasool, Shahid; Rashid, Umer; Hussain Bukhari, Iftikhar; Zubair, Muhammad; Noreen, Mnaza; Abbas, Mazhar (Asian Journal of Chemistry, 2013)
In this work, we evaluated the antimicrobial, cytotoxicity properties of the snapdragon (Antirrhinum majus) extract and fractions. The cytotoxicity, studied by haemolytic activity against human blood erythrocytes assays, indicated a low cytotoxic effect on the absolute methanol extract and its fractions from plant. Chemical analysis of whole plant was also carried out. For chemical analysis HP-LC analysis was carried out to determine the presence of phenolics. The GC-MS analysis was also carried out to determine the presence of some phytoconstituents in n-hexane extract (extracted by soxhlet). The results of present study revealed that snapdragon plant might be considered as a good source of natural antimicrobial.